Nothing special. Volume 3, Pride and pompousness - Cook, Katie, 1981- (Ten Speed Graphic, an imprint of Crown Publishing Group, a division of Penguin Random House Publishing Group, 2025)
"Callie, Declan, Lasser, and Radish find themselves amidst a plot to overthrow fairy royalty in the third installment of the hit Webtoon series Nothing Special, featuring exclusive behind-the-scenes material from the inimitable Katie Cook. Laurel Poppyfield, matriarch of the fairy Poppyfield family, is dying. She holds the majority of the Poppyfields' magic, and has no heir to give it to. Or so she thought until Callie, Declan, Lasser, and Radish walked into the family estate trying to find someone to heal Declan's wing. It turns out Declan is Laurel's grandson and practically fairy royalty, and the timing of his arrival could not be more perfect. Not everyone is happy about Declan's sudden appearance, though. Leir, one of Lasser's older brothers, has worked for years to become a trusted presence in the Poppyfield home. He was Laurel's top choice to inherit the family's magic before Declan showed up, and he's not about to let his plans get ruined. It's up to Callie, Declan, Lasser, and Radish to thwart his nefarious schemes before the Poppyfield magic falls into the wrong hands. The third installment of Katie Cook's Nothing Special collects the final 25 episodes of Season 2 of the webcomic."--Publisher.